Domestic and Multinational Banking. - Weston, Rae (Routledge Library Editions: Banking & Finance., 2013)
This book examines the fundamental nature of banking in the economy of the 1970s and 80s, arguing that banking cannot be properly understood unless it is regarded as the retailing of financial services. In analysing the nature of banking the book demonstrates how banking might operate without regulatory constraints; surveys the patterns of regulatory constraint in a wide range of economies; analysis the effects of these various forms of constraint on the operation of a previously unregulated bank; examines the move to multinational banking; explores risks peculiar to multinational banking.